Local Action Groups - a possible solution to the rural problem of Romania - Ailenei Dorel; Mosora Cosmin (European Regional Science Association (ERSA), 2011)
Romania has the highest share of EU rural areas (44.9% ), which generates and maintains a long series of regional disparities. Because of these disparities, the economy faces a number of elements that undermine the quality of human and social capital and reduces the potential for growth: precarious social and economic infrastructure, reduced access to markets and thus to goods, a low level of both economic cohesion and living standards, and a difficult access to education and training. During the communist era, a forcefully reduction of the rural share was undertaken through various means, most often destructive . Even the transition to a market economy has failed to improve the situation because, in recent years, the urban-rural migration flows have surpassed the rural-urban flows making the too large rural share problem to block the structural changes needed on one hand to modernize the economy, and on the other hand for the European integration. When analyzing the use structure of work resources we observe even greater differences, especially on account of population employed in agriculture. From this perspective, the authors consider that the program impact of sustaining local action groups, LEADER+, extends beyond the horizon of the National Plan of Rural Development , tending to a medium or even long run, when the rural problem of Romania can be solved. Thus the local action groups can contribute to urban areas revitalization and development, through the promotion of economic activities in adjacent rural areas in a manner similar to Lösch's theory. The authors effectuate a diagnosis of the Romanian rural problem and its negative effects. In this framework the implementation progress of local action groups in Romania will be reviewed by testing the main factors that contributed to the organization of local action groups in certain regions of the country.
Keywords: O18; R11; 330; local action groups; regional disparities; economic cohesion; structural changes